2019
DOI: 10.2147/ott.s219777
|View full text |Cite
|
Sign up to set email alerts
|

<p>TRIM3 Negatively Regulates Autophagy Through Promoting Degradation of Beclin1 in Ewing Sarcoma Cells</p>

Abstract: Background and aim: Ewing sarcoma (ES) is an aggressive neoplasm predominantly occurring in adolescents and has a poor prognosis when metastasized. In the current study, we were aiming to investigate the function of TRIM3 in autophagy in ES cells. Methods: The expression of TRIM3 in Ewing sarcoma tissues and normal tissues was examined by quantitative PCR and western blot. The effect of TRIM3 on autophagy was detected by western blot and immunofluorescence assay. Target of TRIM3 was examined by western blot, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…For example, Lys (K) 63linked ubiquitination modulated by Ube2v1 expression enhanced protein aggregation and contributed to Ube2v1's function in regulating protein aggregate formation [30]. However, TRIM3 could directly interact with Beclin1, and improved its K48-linked polyubiquitination, leading to the degradation of Beclin1 and then regulated autophagy [31]. We further demonstrated that UBE2T functions as a tumour promoter in GBM by maintaining the protein level of GRP78.…”
Section: Agingmentioning
confidence: 78%
“…For example, Lys (K) 63linked ubiquitination modulated by Ube2v1 expression enhanced protein aggregation and contributed to Ube2v1's function in regulating protein aggregate formation [30]. However, TRIM3 could directly interact with Beclin1, and improved its K48-linked polyubiquitination, leading to the degradation of Beclin1 and then regulated autophagy [31]. We further demonstrated that UBE2T functions as a tumour promoter in GBM by maintaining the protein level of GRP78.…”
Section: Agingmentioning
confidence: 78%
“…However, the survival rates of patients with metastasis and recurrence are still unacceptable low [2]. To date, accumulating evidences suggest a close relationship between autophagy and ES [21][22][23][24][25][26][27][28]. Here, our finding that ATG2B, ATG10 and DAPK1 are potential protective ARGs with prognostic value in ES is valuable.…”
Section: Discussionmentioning
confidence: 69%
“…There were also many reports indicating that ATG2B was associated with drug resistance by activating autophagy in multiple tumors [10,11]. Although ATG2B had not been reported in ES, but there had been plenty of reports that autophagy was associated with the prognosisi of ES [19][20][21][22][23][24][25][26]. In our study, ATG2B was found to be a potential protective factor in ES, the same as it's in gastric and colorectal carcinomas, breast carcinoma and cutaneous squamous cell carcinoma, but opposite to non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM proteins have been associated with many biological processes, including transcriptional regulation cell differentiation, signaling transduction, and apoptosis. Overexpression of TRIM3 significantly inhibits autophagy through promoting the degradation of Beclin-1, as evidenced by the increases in the amount of P62 (SQSTM1) and the reductions in the amount of LC3B-II, two important markers of autophagy, as well as by the increased LC3 puncta in cells [68].…”
Section: The Impact Of Autophagy In Ewing Sarcomamentioning
confidence: 99%